Music teachers' descriptions of their workplaces in relation to micropolitics*. (27th May 2018) - Conway, Colleen; Rawlings, Jared; Hibbard, Shannan
ABSTRACT: The purpose of this study was to examine the descriptions of workplace experiences of nine music teachers in direct relation to the literature on micropolitics. Research questions were: (a) How did participant music teachers' descriptions of their workplace experiences relate to teachers, administrators, and students (as discussed in the micropolitical literature)? and (b) How can micropolitics be used to understand the similarities and differences between a qualitative comparison of the responses from beginning teacher participants and experienced teacher participants? Findings are presented within Hoyle's [1986. The Politics of School Management . London: Hodder and Stoughton] micropolitical organisational underworld including: (a) cooptation (diversion of potential opposition); (b) displacement (concealing 'real' interests); and (c) controlling information. This secondary analysis study revealed that the vast differences in the negotiations and challenges of beginning and more experienced music teachers, most importantly, the ways in which experienced teachers learned to share power with the stakeholders in their settings. Music teachers both shape and are shaped by their micropolitical context which suggests further analysis of organisational structures and power in the workplace may be more important to understanding music teaching and learning than often assumed.